Fungsi Penyajian Kesenian Jaran Kencak pada Masyarakat di Kabupaten Probolinggo - Safira Fitriya (Mahesa Research Center, 2021)
This article examines the function of the Jaran Kencak performing arts in the community in Probolinggo Regency. Jaran Kencak is classified as a performing art because of its inherent function in community ritual activities. Its appearance is used as an existential symbolic medium during initiation, either for marriage or circumcision (for boys). This research is aimed at understanding the function of the Jaran Kencak performing arts which is supported by the people of Desa Pedagang, Probolinggo Regency. The research method uses descriptive qualitative. The data used are sourced from interviews with Jaran Kencak artists named Isbullah (50 years old) heir to the 3rd generation generation association, and Saman (42 years) as the presenter of Jaran Kencak presentation. Apart from interviews, observations were used at the time of performance to enliven the celebration of the village community. The completeness of the data and to convince the researcher used a documentation review. The data analysis process carried out data codification, data reduction, data presentation, and drawing conclusions. The validity of the data was obtained by triangulation. The analysis uses descriptive interpretation. Research results: 1) Jaran Kencak as a ritual, 2) Jaran Kencak as entertainment